To question about decline of power-hungryness of process electrolysis of aluminium - Червоний, Іван Федорович; Щербань, Геннадій Іванович; Бредіхін, Віктор Миколайович; Маняк, Микола Олександрович; Лукошніков, Ігор Євгенович; Прутцков, Дмитро Володимирович (Eastern-European Journal of Enterprise Technologies, 2012)
Possibility of decline of energy intensity process of aluminum electrolysis is considered during optimization of the magnetohydrodynamic mode of electrolyzed. Periodic adjustment of position of anode with alternation of cycles of automatic serve of alumina revved up circulation of electrolyte